2019
DOI: 10.3390/w11112308
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Various Precipitation Products Using Ground-Based Discharge Observation at the Nujiang River Basin, China

Abstract: Precipitation observation and prediction is difficult in many high elevation regions due to the complex terrain and the lack of in situ observations for comparison. The Nujiang River (upper and middle Salween River) basin in the Tibetan Plateau is no exception. Because of this shortcoming, we propose the use of gauge-observed discharge time series at the basin outlet (e.g., Jiayuqiao hydrological station) to evaluate the performance of four different precipitation products (e.g., satellite-based products and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…MERRA2 exhibits its worst performance in the Upper Sinú subbasin, as all bias values indicate that estimations from this reanalysis product are at least twice as big as the values estimated from the IDEAM time series. This poor performance by MERRA2 in scarcely instrumented and complex areas follows findings from previous studies for other world regions, such as those by Pedreira et al [41], Quagraine et al [35], and Mao et al [75]. On the other hand, the ERA5 performance for monthly rainfall estimations in mountain areas has shown mixed results.…”
Section: Discussionsupporting
confidence: 84%
“…MERRA2 exhibits its worst performance in the Upper Sinú subbasin, as all bias values indicate that estimations from this reanalysis product are at least twice as big as the values estimated from the IDEAM time series. This poor performance by MERRA2 in scarcely instrumented and complex areas follows findings from previous studies for other world regions, such as those by Pedreira et al [41], Quagraine et al [35], and Mao et al [75]. On the other hand, the ERA5 performance for monthly rainfall estimations in mountain areas has shown mixed results.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, Singh and Saravanan (2020) [35] evaluated four rainfall products for the Wunna Riveris catchment in India and found that the Global Precipitation Climatology Project (GPCP) rainfall data, TRMM and APHRODITE to be more suitable products for the simulation of hydrological processes in India. Mao et al (2019) [36] evaluated three rainfall products, namely GLDAS, TRMM, China Meteorological Forcing Dataset (CMFD) and MERRA-2. They assessed that, for runoff simulation, MERRA-2 performed better for the Nujiang River basin, China.…”
Section: Rainfall Datasetsmentioning
confidence: 99%
“…In light of this, some researchers have modified global land-cover maps by incorporating additional data sources to achieve the necessary specificity for their particular study. For instance, Mao et al (2019) [36] modified the GLCC data with glacier coverage data from the International Center for Integrated Mountain Development (ICIMOD) for Nujiang River basin, China. Similarly, Soulis et al (2020) [60] updated the CORINE land cover with data from the Integrated Administration and Control System, Greece, (IACS) for the agricultural part to be used in the distributed hydrological modelling of Greece.…”
Section: Land-use Land-change Datasetsmentioning
confidence: 99%
See 2 more Smart Citations